What is the future of immunotherapy in multiple myeloma? - Rasche, Leo; Hudecek, Michael; Einsele, Hermann (Blood, 2020)
The treatment of multiple myeloma (MM) is currently being redefined by humoral and cellular immunotherapies. For decades, there was limited belief in immune-based anti-MM therapy as a result of the moderate graft-versus-myeloma effect of allogeneic stem cell transplantation. Today, monoclonal antibodies comprise the new backbone of anti-MM therapy, and T-cell therapies targeting BCMA are emerging as the most potent single agents for MM treatment. Herein, we present our assessment of and vision for MM immunotherapy in the short and midterm. (Blood. 2020;136(22): 2491-2497)
CRIS-Team Scopus Importer:2023-03-23